A Scale Development Approach to the Role of Word of Mouth in Selection of Snack Food Eateries - Justus, T. Frank Su nil; Sunitha, T. (Gyan Management Journal, 2016)
Word of mouth communication involves an one to one personal communication which the receiver gets from a worthy person who has earlier tried the product and who has no commercial connection with the product or shop. Word of mouth arises because of the propensity of people to discuss the pros and cons of a new purchase with likeminded others who can share their passion and when the other person gets influenced by this communication there is likelihood that the person will purchase the product. The manuscript makes an attempt to identify the influence of traditional word of mouth in choice of eatery. The data was collected using convenience sampling method through personal interview and a total oflSO respondents who accepted to have been influenced through word of mouth communication within the last three months were chosen for the survey. The model fit indices indicated the model as an acceptable to identify the dimensions of the influence of word of mouth in selection of snack food eateries. The dimensions that influenced word of mouth were identifies as credibility, quality, hygiene, decision, time and social attributes. This scale would be highly useful to eatery owners to understand the dimensions through which word of mouth can influence consumers. In future the studies can be made to understand the dimensions of word of mouth that influence purchase of automobiles, mobile phones and also store choice among apparel shoppers. Consumers often need more than an advertisement communication to give a product or a shop a try. Hence an endorsement in a one to one communication by a real user whose approach the consumer feels as sincere often makes a major push in enabling the consumer to try the product, shop or service. Hence word of mouth communication can be defined as one to one personal communication which the receiver gets from a worthy person who has earlier tried the product and who has no commercial connection with the product or shop. Word of mouth ensures the customer gets motivated by an authentic user and on the other side the confession of dissatisfied consumers can provide a feeling of disapproval. Hence the word of mouth is a double edged sword that can be either positive or negative. Positive word of mouth has the clout to be the biggest differentiator among competing brands or stores.
Keywords: commercial; communication; product; credibility; quality; decision; hygiene